Antioxidant Content, Capacity and Retention in Fresh and Processed Cactus Pear (Opuntia ficus-indica and O. robusta) Fruit Peels From Different Fruit-Colored Cultivars - De Wit, Maryna; Du Toit, Alba; Osthoff, Gernot; Hugo, Arno (Frontiers in Sustainable Food Systems, 2020)
During processing, the peels and seeds from cactus pear fruits are usually discarded. These “waste” products contain valuable bioactive compounds. This study investigated the antioxidant content and antioxidant potential of fresh and processed (juiced, dried, preserved, and chutney) cactus pear fruit peels from different fruit-colored cactus pear cultivars. Cactus pear peels contained high levels of antioxidants and demonstrated high antioxidant activity. The highest contents were found in dried peels, while the preserves had the lowest contents. Products on the positive side of Factor 1 of the PCA plot are mostly associated with the antioxidants PCA analysis showed that products, rather than cultivars, seem to cluster together, e.g., juices and fresh peels, chutneys, preserves and dried peels. Robusta and its products cluster together, as well as with betalains. The % DPPH, carotenoids and phenolics are grouped together, with % chelating activity closely correlated with ascorbic acid. Dried products from all cultivars correlated closely with % DPPH, carotenoids and phenolics, especially dried peel from Gymno-Carpo (orange), Ofer (orange), Meyers (red), and Nepgen (green). Red and orange preserves formed a cluster, while green preserves and chutney from all cultivars clustered together, as did fresh peels and juices. Purple fruit peel products had the highest % DPPH, % chelating activity, betalains, phenolic compounds and carotenes. Ascorbic acid dominated in orange and red fruit peels. Purple and orange were the colors of cactus pear fruit cultivars that might be the best choice in terms of antioxidant content. The cultivar that presented the best fruit peel from an antioxidant point of view for preservation was Robusta. Cactus pear fruit peels should be included in processed products such as juice, dried fruit and chutneys. These processed products are multi-component food ingredients and are therefore multi-component nutraceuticals which retained their antioxidant properties.